Between Fear and Freedom: Essays on the Interpretation of Jeremiah 30–31. By Bob Becking. Pp. viii + 338. (Oudtestamentische Studiën, 51.) Leiden: Brill, 2004. isbn 90 04 14118 9. €90/120 - Bultmann, Christoph (The journal of theological studies, 2006)
The book offers a translation and structural analysis of Jer. 30:1–31:40 and five exegetical studies of Jer. 30:5–11; 30:12–17; 31:15–22; 31:29–30; 31:31–7 respectively. It is designed to throw new light on the sequence of visions for a future of Jacob (Israel) in its land and the culmination of this sequence in the idea of a new covenant. As the subtitle indicates, the studies (pp. 135–272) are revised versions of earlier essays, published between 1989 and 2003. Becking advocates a shift in methodological orientation in Old Testament exegesis. While historical issues, including the question of the literary growth of individual texts and the redaction history of a wider literary complex, are reduced to a question of ‘context’ and find a very general answer (cf. esp. pp.